Abdominal pain : - Nyhus, LIoyd M. (Appleton & Lange, 1995)
This practical text, with essays by 17 doctors, focuses on the diagnosis & treatment of acute abdominal pain. Non-surgical causes of abdominal pain & abdominal diseases are covered. The book emphasizes the detailed analysis of a patient's symptoms & complaints, as well as the signs noted on the physical examination; describes specific disease entities that cause abdominal pain; highlights laparoscopy, abdominal trauma, the immuno-compromised patient, & non-surgical causes of acute abdominal pain. Provides algorithms & tables for quick referral. Illustrated with photographs, charts, & drawings.